PENINGKATAN KEMANDIRIAN DAN PRESTASI BELAJAR PEMROGRAMAN DASAR SISWA KELAS XI MULTI MEDIA MELALUI PEMANFAATAN MODUL DI SMK NEGERI 1 MEMPAWAH HULU - MARSELUS, S.E., M.M., M.Pd (Yudha English Gallery, 2020)
Abstract The aims of this research to improve the self-direction learning and learning achievement in Basic Programming learning of students through the utilization of Basic Programming module in 11th Grade of Multimedia 2 in SMK Negeri 1 Mempawah Hulu.This research is classroom action research which was conducted in two cycles. Every cycle consists of 4 stages: (1) Planning, (2) Implementation of action, (3) Observation, (4) Reflection. The subject of this research is 11th Grade of Multimedia 2 SMK Negeri 1 Mempawah Hulu in 2nd semester with total number of students 30. Data collection techniques that had been used is the the observation sheets of self-direction learning, questionnaires, evaluation test, documentation. Data analyzed by descriptive statistical analysis. The results showed that the utilization of Basic Programming module can improve the self-directed learning Basic Programming in 11th Grade of Multimedia 2 students in SMK Negeri 1 Mempawah Hulu. Improvement can be seen from the average score of self-directed learning. In the pre-action, the average score was 4.5 with a 16% percentage in very less category, increasing in cycle I to 13.4 with a 47% percentage in good category and increasing again in cycle II to 25.1 with percentage 89 % in very good category. Increased self-directed learning is in the indicators of student learning motivation, use of learning resources, learning strategies, self-monitoring, self- evaluation in learning, and environmental factors. Improvement student’s learning achievement can be seen by the increased percentage mastery of student’s learning achievement. Percentage mastery of student’s learning achievement in cycle I 63,3% with average value 72,7 in good category increase in cycle II to 93,3% with average value 86,2 in very good category.Keywords : self-directed learning, students learning achievement, Basic programming, Basic Programming module.